Visual analysis and comparison of data from two databases on global competence: Using the Cite Space knowledge graph - Ma, Wenjuan; Chang, Tingzhi; Hong, Wilson Cheong Hin; Xu, XiaoShu; Zhang, YunFeng (International Journal of Innovative Research and Scientific Studies, 2023)
This study uses the Social Sciences Citation Index (SSCI) database from 1997 to 2022 and the Chinese National Knowledge Infrastructure (CNKI) from 2008 to 2022 to analyse global competence in order to examine the present condition of global competence research. The results showed a rising trend in global competence where the United States was in the leading position and China ranked second in academic publications but its influence was relatively weak. According to a keyword analysis, "global competence," "education," "model," "globalization" and "global governance" were the most prevalent topics. The keyword time map analysis generated three periods of 'global competence research: the embryonic stage before 2010, the initial exploration period from 2011 to 2016 and the development period from 2017 until now. Future studies should concentrate on developing a theoretical framework for localization and creating practical assessment tools based on the framework. Implementation strategies must also be actively investigated.